EVALUASI PELAKSANAAN AKADEMIK FAKULTAS USHULUDDIN ADAB DAN HUMANIORA, INSTITUT AGAMA ISLAM NEGERI PURWOKERTO 2015-2020 - Arif Hidayat; Hartono; Futihat Rizqi Amalia (Jurnal Evaluasi Pendidikan, 2022)
This study aims to reveal the process of academic implementation, achievements and not yet achieved and strategies for achieving and following up on academic implementation at the Faculty of Ushuluddin Adab and Humanities, State Islamic Institute of Purwokerto 2015-2020. The approach used in this research is a qualitative approach. Data collection and data verification were carried out with FGDs from leaders, lecturers, and education staff. The results of this study reveal that academic implementation at the Faculty of Ushuluddin Adab and Humanities, State Islamic Institute of Purwokerto 2015-2020 has been carried out based on curriculum revisions that refer to the determination of graduate profiles, learning outcomes, determination of study materials, determination of courses, and curriculum preparation. To support the learning system, a semester learning plan (RPS) is prepared.